2015
DOI: 10.1016/j.bbagrm.2014.06.001
|View full text |Cite
|
Sign up to set email alerts
|

TLX: A master regulator for neural stem cell maintenance and neurogenesis

Abstract: The orphan nuclear receptor TLX, also known as NR2E1, is an essential regulator of neural stem cell (NSC) self-renewal, maintenance, and neurogenesis. In vertebrates, TLX is specifically localized to the neurogenic regions of the forebrain and retina throughout development and adulthood. TLX regulates the expression of genes involved in multiple pathways, such as the cell cycle, DNA replication, and cell adhesion. These roles are primarily performed through the transcriptional repression or activation of downs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 109 publications
1
72
0
1
Order By: Relevance
“…In adult mouse brains, TLX functions as a transcriptional repressor that is critical for the regulation of neurogenesis and the progression of neural stem cell-dependent gliomagenesis (Sun et al 2007;Liu et al 2008Liu et al , 2010Zou et al 2012). Thus, TLX has been suggested as a therapeutic target for the treatment of human neurological disorders and brain tumors (Islam and Zhang 2014), and a recent study showed that TLX activity can be regulated by small molecules (Benod et al 2014). These exciting findings suggest that our crystal structures of TLX may also provide a rational template to develop drugs for the treatment of TLX-related diseases.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In adult mouse brains, TLX functions as a transcriptional repressor that is critical for the regulation of neurogenesis and the progression of neural stem cell-dependent gliomagenesis (Sun et al 2007;Liu et al 2008Liu et al , 2010Zou et al 2012). Thus, TLX has been suggested as a therapeutic target for the treatment of human neurological disorders and brain tumors (Islam and Zhang 2014), and a recent study showed that TLX activity can be regulated by small molecules (Benod et al 2014). These exciting findings suggest that our crystal structures of TLX may also provide a rational template to develop drugs for the treatment of TLX-related diseases.…”
Section: Discussionmentioning
confidence: 93%
“…Both TLX and Atrophin are conserved proteins that play important physiological roles in mammals and insects (Gui et al 2011;Islam and Zhang 2014). In adult mouse brains, TLX functions as a transcriptional repressor that is critical for the regulation of neurogenesis and the progression of neural stem cell-dependent gliomagenesis (Sun et al 2007;Liu et al 2008Liu et al , 2010Zou et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of retinopathies also result from Tlx mutation, indicating that it plays a critical role in the development and maintenance of retinal cells [162]. Tlx plays a role in neural stem cell self-renewal and adult neurogenesis [163], where it functions upstream of a Wnt signaling pathway [164]. In mutant Tlx mice, neural stem cells undergo precocious maturation to neurons and are therefore quickly depleted, resulting in mice with smaller gyrus and forebrain regions [165,166].…”
Section: Tll/nhr-67/tlx (Nr2e1)mentioning
confidence: 99%
“…For example, Beyaz and colleagues identified peroxisome proliferator-activated receptor-δ (PPAR-δ) and its heterodimeric binding partners liver/retinoid X receptor (LXR/RXR) as mediators of fatty acid-induced enhancement of intestinal stem cell proliferation and self-renewal, despite evidence that PPAR-δ is dispensable for normal intestinal stem cell function [62]. Another example is the nuclear receptor Tailless (TLX), which is directly required for the maintenance and proliferation of mammalian neural stem cells [63]. Gene knockout approaches in mammals for other nuclear hormone receptors, such as the Retinoic Acid Receptor, have yielded mixed results, possibly due to considerable functional redundancy between receptors [64].…”
Section: Introductionmentioning
confidence: 99%